Anthropology of meningitis in Niger. Epidemics spaces, scientific mobilizations and representations of illness - (:unkn) unknown (My University, 2013)
The Epidemic of meningitis is a public health problem historically rooted in the Nigerian society. More than a century ago the phenomenon was reported in Niger, often considered as the epicenter of a space called "the meningitis belt". In the 21st century, epidemics of meningitis become moments of great scientific and political mobilization by major disturbances they cause (more than 3000 death in 1995). The large number of people affected as well as the fast spreading of the disease condemning to death the patient just 24 hours after its appearance, makes it one of the most dreaded diseases in Niger. In the early 1960's, the World Health Organization send a French military physician Léon Lapeyssonnie to rescue Niger. Indeed, the WHO wanted the meningitis epidemics to become one of the major transmitted diseases to control. By identifying temporal sequences of meningitis over half a century, Léon Lapeyssonnie had succeeded in making meningitis not only "a specifically African problem", but also a tropicalized disease, that is to say, confined within a guilty ecological space extending from west Africa to east Africa including geographic coordinates that help identify epidemics in a social space. Contemporary anthropology shows that this phenomenon has evolved and that important issues on public, social and political health evolve around the control of this disease in Niger. Overpowered by the paradigm of epidemiology, the Government of meningitis epidemics is being hindered by strong scientific controversies for more than a decade while even so we are on the turning point of a epidemiological change. What can anthropology teach us on the building up of a pathological phenomenon as complex as meningitis linking ecology, medicine and society? This thesis at the junction of medical anthropology and the sociology of science tends to see how meningitis was built as a public health problem in Niger. I am particularly interested in what appears to be a para
Keywords: African Research